Robust Binding between Carbon Nitride Nanosheets and a Binuclear Ruthenium(II) Complex Enabling Durable, Selective CO2 Reduction under Visible Light in Aqueous Solution. Issue 17 (7th April 2017) - Kuriki, Ryo; Yamamoto, Muneaki; Higuchi, Kimitaka; Yamamoto, Yuta; Akatsuka, Masato; Lu, Daling; Yagi, Shinya; Yoshida, Tomoko; Ishitani, Osamu; Maeda, Kazuhiko
Abstract: Carbon nitride nanosheets (NS‐C3 N4 ) were found to undergo robust binding with a binuclear ruthenium(II) complex (RuRu′ ) even in basic aqueous solution. A hybrid material consisting of NS‐C3 N4 (further modified with nanoparticulate Ag) andRuRu ′ promoted the photocatalytic reduction of CO2 to formate in aqueous media, in conjunction with high selectivity (approximately 98 %) and a good turnover number (>2000 with respect to the loaded Ru complex). These represent the highest values yet reported for a powder‐based photocatalytic system during CO2 reduction under visible light in an aqueous environment. We also assessed the desorption ofRuRu ′ from the Ag/C3 N4 surface, a factor that can contribute to a loss of activity. It was determined that desorption is not induced by salt additives, pH changes, or photoirradiation, which partly explains the high photocatalytic performance of this material. Abstract : Fixed to fix : Carbon nitride nanosheets bind strongly with a binuclear ruthenium(II) complex even in basic aqueous solution, enabling durable, selective CO2 reduction into formate under visible light.